2013
DOI: 10.1039/c2nr31982a
|View full text |Cite
|
Sign up to set email alerts
|

Single gold trimers and 3D superstructures exhibit a polarization-independent SERS response

Abstract: Dimers of metal nanospheres are well-known for their characteristic anisotropic optical response. Here, we demonstrate in single-particle SERS experiments that individual gold trimers and 3D superstructures exhibit a polarization-independent SERS response. This optical behavior of single particle clusters provides constant SERS signals, independent of the mutual orientation of the incident laser polarization and the plasmonic nanostructure, which is desired or even required in many SERS applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
26
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 32 publications
2
26
0
Order By: Relevance
“…In contrast to dimers, trimers exhibit a quasi-polarization-independent optical response. [41] Overall, the correlated HR-TEM/SERS experiments demonstrated that all highly SERS-active dimer and trimer nanoantennas exhibited either coalesced or separated cores with gap sizes in the range < 1 nm, a finding in accordance with results from finite element method (FEM) calculations.…”
Section: Experimentally Determined Distance Dependence Of Sers In a Dsupporting
confidence: 78%
See 1 more Smart Citation
“…In contrast to dimers, trimers exhibit a quasi-polarization-independent optical response. [41] Overall, the correlated HR-TEM/SERS experiments demonstrated that all highly SERS-active dimer and trimer nanoantennas exhibited either coalesced or separated cores with gap sizes in the range < 1 nm, a finding in accordance with results from finite element method (FEM) calculations.…”
Section: Experimentally Determined Distance Dependence Of Sers In a Dsupporting
confidence: 78%
“…Additionally, a quasi-isotropic optical response-in contrast to the characteristic j cos q j 2 dependency for dimers (where q is the angle between laser polarization and dimer axis)-is theoretically expected [46] and has been demonstrated experimentally at the single-particle level. [41] Figure 9 shows electron microscopy images from 3D SERS-active superstructures obtained by self-assembly. Gold particles (80 nm) were incubated with Raman reporters and encapsulated with a very thin silica shell (Figure 9 a), [46] using a protocol described in Section 4.1.1.…”
Section: Plasmonic 3d Superstructures Through Self-assembly Of Satellmentioning
confidence: 99%
“…In contrast to NP dimers, assemblies of NPs exhibit a quasi-polarization-independent SERS response at the single-particle level. 33 In further studies the silica-60 encapsulated 3D superstructures may be used as SERS labels in bioanalytical and biomedical applications, e.g. in SERS microscopy for tissue-based cancer diagnostics.…”
Section: Characterizationmentioning
confidence: 99%
“…Besides, molecule will be absorbed on noble metal arrays nanostructures, and nanostructures need to be cleaned before the next application so it cannot be used in real‐time, continuous SERS detection . In addition, in practical SERS detection, many current arrays nanostructure substrates have troubles in polarization‐dependent of excitation light . The optimal‐enhanced direction is determined by the nanostructure morphology, and different nanostructures have completely different optimal‐enhanced directions.…”
Section: Introductionmentioning
confidence: 99%